The Art of Communication and Business in the Explosives Industry - Joseph Meyers (International Society of Explosives Engineers)
Explosives techniques and technology are constantly evolving and improving, yet basic communication and business skills are not being used regularly. Many potential blasting projects never occur due to simplistic, basic factors, such as a lack of communication. Articulate communication is the key component in the blast approval process, which has changed remarkably from how business was conducted fifty years ago. Imperative to the approval process is communication outlining the safety and benefits of the blasting project. Information and transparency with the stakeholders and the Authority Having Jurisdiction (AHJ) will greatly improve the chances of having a blasting project approved. This open communication starts at the inception of the project when the memorandum of understanding (MOU) is obtained, and involves the AHJ through all steps of the approval process. The blasting industry and regulators must work collaboratively to improve safety, security, regulations and licensing. Implementing state of the art blasting techniques, security, safety measures, vibration monitoring and strict licensing allows the AHJ and all stakeholders to remain integrated and informed, contributing to process approval. Regulatory operators should strive to achieve success thru communication, cooperation and compliance which is accomplished thru continued education and transparency. These steps, combined with regular meetings, has proven to be a benefit to both industry and regulators. Relationships are built through trust, teamwork, transparency and communication –including the take holders and AHJ in the approval process from the inception solidifies these relationships and improves teamwork